Stochastic ordering of simulated rugby match activity produces reliable movements and associated measures of subjective task load, cognitive and neuromuscular function - Mullen, T.; Twist, C.; Highton, J. (Journal of Sports Sciences, 2019)
The study assesses the test-retest reliability of movement and physiological measures during a simulated rugby match that employed activities performed in a stochastic order. Twenty male rugby players (21.4 ± 2.1 y) completed two trials of a 2 × 23 min rugby movement simulation protocol during which the order of events was performed in a stochastic order, with 7-10 days between trials. Movement characteristics, heart rate (HR), RPE, maximum voluntary contraction (MVC), voluntary activation (VA%) of the quadriceps, Stroop test and subjective task load rating (NASA-TLX) were measured. The most reliable measures of external load was relative distance (typical error [TE] and CV% = 1.5-1.6 m/min and 1.4-1.5%, respectively), with all other movement characteristics possessing a CV% <5%. The most reliable measure of internal load, neuromuscular function and perceptual measures were for %HRmax (TE and CV% = 1.4-1.7% and 1.4-2.1%, respectively), MVC before (TE and CV% = 10.8-14.8 N/m and 3.8-4.6%, respectively), and average RPE (TE and CV% = 0.5-0.8 AU and 3.6-5.5%, respectively). The Stroop test, NASA-TLX and blood lactate produced the least reliable measures (CV% >5%). Future studies can confidently examine changes in several perceptual, neuromuscular, physiological and movement measures related to rugby activity using stochastic movements.